Development of polycrystalline yttrium aluminum garnet (YAG) fibers. Issue 15 (December 2015) - Kim, Hyun Jun; Fair, Geoff E.; Hart, Allison M.; Potticary, Santeri A.; Usechak, Nicholas G.; Corns, Randall G.; Hay, Randall S.
Abstract: Polycrystalline yttrium–aluminum garnet (YAG) fibers are attractive for high-power lasers and for high-temperature structural materials. Processing methods for <30 μm diameter polycrystalline YAG fibers suitable for single-mode laser operation are presented. The methods use extrusion of classified YAG powders with binders. Extrusion rheologies and rates, and heat-treatment temperatures, times, and environments that yield the most dense, defect-free fibers were explored. Fiber tensile testing, followed by fractography, was used to identify defects and to guide determination of optimal processing conditions. The effects of processing variables on fiber microstructures and properties are discussed. Advantages and disadvantages of processing methods are compared.